Evaluating a new wearable lactate threshold sensor in recreational to highly trained cyclists - Driller, M.; Borges, N.; Plews, D. (Sports Engineering, 2016)
The determination of a cyclist`s lactate threshold (LT) has become an important test performed in sports science laboratories around the world. A limitation of such testing is that it is relatively expensive and invasive, requiring multiple blood samples. The purpose of the current study was to evaluate a commercially available, wearable lactate threshold sensor (WLT) that uses near infrared LED technology to measure gastrocnemius muscle oxygenation and predict LT. The WLT was compared to four traditional calculations of determining LT following an incremental exercise test. Ten male and five female recreational to elite cyclists (mean ± SD; age 24 ± 8, body mass 69.7 ± 7.3 kg, VO2max; 59.7 ± 9.9 ml kg-1 min-1) performed an incremental cycling test to exhaustion. Blood lactate samples were taken at the end of each 3-min stage during the test to determine lactate threshold using four traditional methods (TradLT, Dmax, mDmax, OBLA). Traditional methods were then compared against the WLT predicted value. The correlation between the WLT and TradLT, Dmax, mDmax and OBLA were all >r = 0.96. The highest level of agreement for the WLT was with the Dmax method (95 % limits of agreement: ±17 W, TEE = 8.6 W, 4.4 %). The 95 % level of agreement between the WLT and all other traditional methods was <±40 W (TEE <18 W, 8 %). In summary, the WLT is practical, easy to use and exhibits an acceptable level of agreement with four of the traditionally accepted methods of determining lactate threshold.